Morphological and genetic description of Moniliformis necromysi sp. n. (Archiacanthocephala) from the wild rodent Necromys lasiurus (Cricetidae: Sigmondontinae) in Brazil. (2020) - Gomes, A.P.N.; Costa, N.A.; Gentile, R.; Vilela, R.V.; Maldonado, A.
Abstract: A new species of Moniliformis Travassos, 1915 (Acanthocephala: Moniliformidae) is described from the hairy-tailed bolo mouse, Necromys lasiurus Lund, 1840 (Cricetidae: Sigmondontinae), captured in the Brazilian Cerrado, in Uberlândia, state of Minas Gerais, Brazil. The specimens were studied by light and scanning electron microscopy. Molecular phylogenies were inferred from partial nuclear large subunit ribosomal RNA gene sequences and partial mitochondrial cytochrome c oxidase subunit I gene. The new species is distinguished from other moniliformid species by the number of rows and number of hooks per row, size of the proboscis, size of the eggs, host species and geographical distribution. Molecular phylogenies and genetic distances analyses demonstrated that Moniliformis necromysi sp. n. forms a well-supported monophyletic group with sequences of other species of Moniliformis and is distinguished from them, which agrees with the morphological characteristics, allocating the new species to this genus and to the family Moniliformidae Van Cleave, 1924. This is the first moniliformid acanthocephalan described from a wild rodent in Brazil.